Preparation method and application of composite quasi-solid electrolyte based on covalent organic framework nanofiber membrane
By using covalent organic frame nanofiber membranes to prepare composite quasi-solid electrolytes in solid-state lithium batteries, the problem of high lithium ion migration barrier at low temperatures is solved, and the high capacity and stability of lithium batteries under low temperature conditions is achieved.
Patent Information
- Application Number
- CN202411766684.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-11
AI Technical Summary
Solid-state lithium batteries have high lithium ion migration barriers at low temperatures, resulting in low capacity and poor stability of lithium batteries.
Using a composite quasi-solid electrolyte based on covalent organic frame nanofiber membrane, nanofiber membranes are prepared by electrospinning, and fluorinated covalent organic frameworks are grown on them in situ to form a multi-stage pore network structure to improve the efficiency of lithium ion transmission.
It realizes efficient transmission of lithium ions under low temperature conditions, improves the capacity and stability of solid-state lithium batteries, reduces the interface impedance, and enhances the safety of the battery.
Smart Images

Figure CN119601763A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state lithium batteries, and in particular to a preparation method of a composite quasi-solid-state electrolyte based on a covalent organic framework nanofiber membrane and an application thereof. Background Art
[0002] As an efficient energy storage device, lithium batteries have been widely used in portable electronic devices, electric vehicles, energy storage systems and other fields. Traditional liquid electrolytes are volatile and flammable, and pose serious safety hazards under extreme conditions such as external impact and overheating. In addition, the theoretical energy density is not high and cannot meet the needs of development. Replacing traditional liquid electrolytes with solid electrolytes can significantly improve battery safety, and can also be matched with lithium metal negative electrodes to prepare solid-state lithium metal batteries, achieving higher energy density and providing more powerful power support for the development of electric vehicles and other fields.
[0003] Although solid-state lithium batteries have great advantages, their ability to cope with complex environments needs to be improved. In low-temperature environments, the ionic conductivity of solid electrolytes decreases significantly, and problems such as insufficient charge transfer kinetics at the electrolyte-electrode interface lead to a serious decrease in the capacity and stability of the battery. Under high-temperature conditions, the stability of solid electrolytes deteriorates, and problems such as interfacial side reactions seriously limit the performance and stability of solid-state lithium batteries. In order to overcome the problems of low low-temperature capacity and poor high-temperature safety of existing solid-state lithium batteries, it is still necessary to study a new type of composite solid electrolyte that can maintain good ionic conductivity and stability in a lower temperature range, providing strong technical support for the practical application of solid-state lithium batteries.
[0004] Covalent organic framework material is an organic porous polymer with the characteristics of easy functionalization, high temperature resistance, light weight, uniform pore size, high porosity, etc. It can effectively solve the problems of poor high temperature resistance, lithium dendrite growth, low ion conductivity, etc. of polymer solid electrolytes, and has attracted the attention of researchers in the field of solid electrolytes. However, on the one hand, the ion conductivity of solid electrolytes is low at low temperatures, resulting in low capacity and poor cycle stability of lithium batteries. Therefore, how to reduce the activation energy of lithium ion transmission and the barrier of lithium ion migration through the skeleton design of covalent organic frameworks, so that lithium ions can be more easily moved and transmitted at low temperatures is an urgent problem to be solved. On the other hand, covalent organic frameworks have rigid skeletons, are insoluble, difficult to process, and have rigid interface contact with electrodes, resulting in high interface impedance. Therefore, how to prepare thin and flexible solid electrolytes, reduce the migration distance of lithium ions, and reduce interface impedance is of great significance to the development of solid electrolytes.
[0005] Invention content: The technical problem to be solved by the present invention is that the solid electrolyte has a high barrier to lithium ion migration at low temperatures, which limits the migration of lithium ions and leads to low capacity and poor stability of lithium batteries. The present invention utilizes the unique functional skeleton and microporous structure of the covalent organic framework and the high flux characteristics of the nanofiber membrane to invent a composite quasi-solid electrolyte based on a covalent organic framework nanofiber membrane with high lithium ion selectivity, low lithium ion transfer activation energy, multi-level pore mass transfer enhancement and flexible processability.
[0006] The first aspect of the present invention provides a method for preparing a composite quasi-solid electrolyte based on a covalent organic framework nanofiber membrane, characterized in that it comprises the following steps:
[0007] Step 1: dissolving polyacrylonitrile and 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine monomers in N,N-dimethylformamide, preparing a nanofiber membrane rich in one monomer by electrospinning, and then in situ growing a fluorinated covalent organic framework on the nanofiber membrane by a Schiff base reaction with tetrafluoroterephthalaldehyde monomer, and drying and hot pressing to obtain a nanofiber membrane based on a fluorinated covalent organic framework;
[0008] Step 2: preparing a precursor solution consisting of dioxolane, ethylene glycol dimethyl ether, fluorinated ethylene carbonate, and lithium salt;
[0009] Step 3: adding the precursor solution into the covalent organic framework nanofiber membrane to carry out an in-situ polymerization reaction, thereby obtaining the composite quasi-solid electrolyte;
[0010] Furthermore: in the step 1, the mass fraction of polyacrylonitrile is 10%-15%, and the ratio of polyacrylonitrile to 2,4,6-tris(4-aminophenyl)-1,3,5-triazine monomer is 2:1, 1:1 or 1:2.
[0011] Further: in the step 1, the electrospinning rate is set to 0.5-2 mL h-1, the working voltage is 10-20 kV, and the distance between the needle and the collector is 10-20 cm.
[0012] Further: In the step 1, the specific step of in-situ growth is to dissolve 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine and tetrafluorobenzaldehyde in 8 mL of n-butanol, 8 mL of o-dichlorobenzene and 0.8 mL of acetic acid (12 mol L -1 ) as the reaction liquid, then put the monomer fiber membrane and the reaction liquid into a reactor for reaction at 60-150° C. for 1-7 days, and rinse and soak with tetrahydrofuran, methanol and n-hexane for three times.
[0013] Furthermore: the molar ratio of 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine in the reaction solution and the monomer fiber membrane is 1:1, and the molar ratio of 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine and tetrafluorobenzaldehyde in the entire reaction system is 1:1.5.
[0014] Furthermore: in the step 2, the volume fraction of dioxolane is 50%-80%, the volume fraction of ethylene glycol dimethyl ether is 10%-40%, and the volume fraction of fluorinated ethylene carbonate is 10%.
[0015] Further: the lithium salt in step 2 is lithium bis(trifluoromethylsulfonyl)imide and lithium hexafluorophosphate, and the concentration of the two is 0.5-1 mol L -1 .
[0016] Furthermore: in step 3, the temperature of the in-situ polymerization is 30-60° C., and the reaction time is 2-24 hours.
[0017] The second aspect of the present invention provides a composite quasi-solid-state lithium battery based on a covalent organic framework nanofiber membrane, which is prepared using the low-temperature composite quasi-solid-state electrolyte, positive electrode material, and negative electrode material. The specific steps are to drop the precursor liquid into the covalent organic framework nanofiber membrane, assemble a button cell, and then perform an in-situ polymerization reaction to obtain the composite quasi-solid-state lithium battery.
[0018] The third aspect of the present invention provides an application of the above-mentioned composite quasi-solid electrolyte based on covalent organic framework nanofiber membrane in a solid-state lithium battery, wherein the solid-state lithium battery comprises a composite quasi-solid-state electrolyte, a positive electrode material, and a negative electrode material, wherein the positive electrode material comprises any one of lithium iron phosphate or nickel-cobalt-manganese ternary material electrodes, and the negative electrode material comprises any one of metallic lithium, graphite, and silicon-carbon negative electrodes.
[0019] The present invention has the following advantages:
[0020] (1) The present invention in situ grows a covalent organic framework on the electrospun nanofiber membrane through the Schiff base reaction, which can form a multi-level pore network structure, provide good mechanical properties, and high ion flux, and the electronegative channels of the fluorine-containing micropores can achieve uniform and efficient transmission of lithium ions.
[0021] (2) The composite quasi-solid electrolyte based on the covalent organic framework nanofiber membrane prepared by the present invention can inhibit the formation of lithium dendrites and improve the safety of lithium batteries.
[0022] (3) The solid-state lithium battery provided by the present invention has excellent electrochemical properties at room temperature and low temperature, and can achieve high capacity and stable charge and discharge performance.
[0023] (4) The preparation process of the present invention is simple, the equipment and machinery are mature, and large-scale production can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the covalent organic framework nanofiber membrane of the present invention.
[0025] Figure 2 It is the X-ray diffraction spectrum of the covalent organic framework nanofiber membrane of the present invention.
[0026] Figure 3 It is a comparison diagram of the composite quasi-solid electrolyte AC impedance and ionic conductivity of the covalent organic framework nanofiber membrane (PAN-FCOF) of Example 1, the commercial polypropylene membrane (PP) of Comparative Example 1, and the polyacrylonitrile nanofiber membrane (PAN) of Comparative Example 2.
[0027] Figure 4 It is an AC impedance diagram of the composite quasi-solid electrolyte based on Example 1 (PAN-FCOF), Comparative Example 1 (PP) and Comparative Example 2 (PAN).
[0028] Figure 5 It is a rate diagram of a solid-state lithium battery assembled based on the composite quasi-solid electrolyte of Example 1 (PAN-FCOF) and Comparative Example 1 (PP) at -10°C.
[0029] Figure 6 It is a rate diagram of a solid-state lithium battery assembled based on the composite quasi-solid electrolyte of Example 1 (PAN-FCOF) and Comparative Example 1 (PP) at 30°C. DETAILED DESCRIPTION
[0030] In order to make the results of the present invention more convincing, the technical solution provided by the present invention is described in detail in combination with the embodiments. The following preferred examples are only for illustrating the present invention, but do not limit the protection scope of the present invention.
[0031] All reagents and instruments used in this example are directly available on the market.
[0032] Example 1
[0033] This example provides a method for preparing a composite quasi-solid electrolyte based on a covalent organic framework nanofiber membrane, comprising the following steps:
[0034] (1) Weigh 0.2 g of polyacrylonitrile, 0.2 g of 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine and 1.8 g of N,N-dimethylformamide to prepare 2 ml of spinning solution. Stir magnetically in a small glass bottle for 6 h. After the solution is fully dissolved, it becomes yellow and transparent, and spinning can be carried out.
[0035] (2) Turn on the electrospinning equipment and adjust the electrospinning rate to 1 mL min -1 , the working voltage was 14 kV, the distance between the spinning needle and the collector was 12 cm, and after the spinning was completed, the obtained 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine monomer / polyacrylonitrile nanofiber membrane was dried at 60 °C for 12 h.
[0036] (3) 41.8 mg of 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine and 73.36 mg of tetrafluorobenzaldehyde were dissolved in 8 mL of n-butanol, 8 mL of o-dichlorobenzene and 0.8 mL of acetic acid (12 mol L -1 ) as the reaction liquid, and then put 83.6 mg of 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine monomer / polyacrylonitrile nanofiber membrane and the reaction liquid into a reactor and react at 120°C for 3 days, rinse and soak with tetrahydrofuran, methanol, and n-hexane three times, and then put into an oven for drying.
[0037] (4) PAN / FCOF was obtained after hot pressing at 120°C and 25 MPa for 1 min.
[0038] (5) Preparing a precursor solution composed of dioxolane, ethylene glycol dimethyl ether, fluorinated ethylene carbonate, and lithium salt, wherein the volume fraction of dioxolane is 60%, the volume fraction of ethylene glycol dimethyl ether is 30%, the volume fraction of fluorinated ethylene carbonate is 10%, and the concentrations of lithium bis(trifluoromethylsulfonyl)imide and lithium hexafluorophosphate are both 1 mol L -1 .
[0039] (6) Adding the precursor solution into the covalent organic framework nanofiber membrane and carrying out an in-situ polymerization reaction at 40° C. for 24 hours to obtain the composite quasi-solid electrolyte.
[0040] (7) When testing the electrochemical properties of the composite quasi-solid electrolyte, it was first assembled in the liquid state and then in-situ polymerized at 40°C.
[0041] Example 2
[0042] This example provides a method for preparing a composite quasi-solid electrolyte based on a covalent organic framework nanofiber membrane, which specifically refers to Example 1, except that the volume fraction of dioxolane in step (5) is changed to 70%, the volume fraction of ethylene glycol dimethyl ether is 20%, and the volume fraction of fluorinated vinyl carbonate is 10%.
[0043] Example 3
[0044] This example provides a method for preparing a composite quasi-solid electrolyte based on a covalent organic framework nanofiber membrane, which is specifically referred to Example 1, except that the concentration of lithium hexafluorophosphate in step (5) is changed to 0.5 mol L -1 .
[0045] Comparative Example 1
[0046] This example provides a method for preparing a composite quasi-solid electrolyte based on a PP membrane, which specifically refers to Example 1, except that the covalent organic framework nanofiber membrane is replaced with a commercially available PP membrane of model Celgard 2400.
[0047] Comparative Example 2
[0048] This example provides a method for preparing a composite quasi-solid electrolyte based on a PAN nanofiber membrane, which specifically refers to Example 1, except that 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine is not added in step (1), and the in-situ polymerization of step 3 is not performed, and the PAN nanofiber membrane is directly prepared and used.
[0049] Microscopic morphology observation, see Figure 1 ,From the scanning electron microscopy images, it can be seen that the covalent organic framework grows evenly on the nanofibers, proving that the ,composite nanofiber diaphragm based on the covalent organic framework was ,successfully prepared.
[0050] Test the X-ray diffraction pattern of the composite nanofiber membrane, see Figure 2 In the X-ray diffraction pattern, the diffraction peak corresponding to COF can be clearly seen. The diffraction peak of COF in the COF / PAN fiber separator also exists, and the intensity of the diffraction peak is very high, indicating that the COF in the fiber has good crystallinity. This regular size of pores plays an important role in the homogenous transmission of lithium ions.
[0051] Test electrochemical performance, see Figure 3 and Figure 4 The interface resistance of the composite quasi-solid electrolyte was tested by AC impedance. Figure 3 As shown, the ionic conductivities of the composite quasi-solid electrolytes based on Example 1 (PAN-FCOF), Comparative Example 1 (PP) and Comparative Example 2 (PAN) are 0.83 mS cm -1 , 0.19mS cm -1 , 0.32 mS cm -1It can be concluded that the multi-level pore network structure formed by the covalent organic framework fiber can provide a high ion flux and improve the ionic conductivity of the quasi-solid electrolyte. The electrochemical stability window of the composite quasi-solid electrolyte of Example 1 (PAN-FCOF), Comparative Example 1 (PP) and Comparative Example 2 (PAN) was tested by linear sweep voltammetry. Figure 4 As shown, the composite quasi-solid electrolyte prepared in Example 1 (PAN-FCOF) has a wider electrochemical stability window than that in Comparative Example 1 (PP) and Comparative Example 2 (PAN), indicating that the introduction of the covalent organic framework can enhance the stability of the quasi-solid electrolyte under high pressure.
[0052] Application Examples
[0053] The present invention provides a method for preparing a composite quasi-solid-state lithium battery based on a covalent organic framework nanofiber membrane, using the composite quasi-solid-state electrolyte of Example 1 (PAN-FCOF) and Comparative Example 1 (PP), the positive electrode material is lithium iron phosphate (LFP), and the negative electrode material is lithium metal (Li). During the assembly of the solid-state lithium battery, the precursor liquid is dropwise added to the covalent organic framework nanofiber membrane. After the assembly is completed, an in-situ polymerization reaction is carried out at 40° C. for 24 hours to obtain a solid-state lithium battery, which is recorded as LFP / PAN-FCOF / Li and LFP / PP / Li full batteries.
[0054] Test the rate performance after assembling into a full battery, see Figure 5 and Figure 6 At -10°C, the LFP / PAN-FCOF / Li full cell exhibited better rate performance, with a capacity of 92 mAh g at 0.1C. -1 The discharge capacity at 1C decreased to 42 mAh g -1 , but significantly higher than the 18 mAh g of LFP / PP / Li -1 At room temperature of 30°C, the LFP / PAN-FCOF / Li full battery also showed better rate performance, with a discharge capacity of 169 mAh g at 0.5C. -1 High specific capacity, greater than 163 mAh g of LFP / PP / Li -1 At a high current density of 5C, the LFP / PAN-FCOF / Li full cell exhibited a high performance of 128 mAh g -1 The discharge specific capacity is also greater than that of LFP / PP / Li. The above results prove that the composite quasi-solid electrolyte based on covalent organic framework nanofiber membrane can ensure that the solid-state lithium battery maintains excellent rate performance at room temperature and low temperature, and can achieve rapid charge and discharge at high current density.
[0055] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and equivalent changes made by using the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite quasi-solid electrolyte based on a covalent organic framework nanofiber membrane, characterized in that: The following steps are involved: Step 1: dissolving polyacrylonitrile and 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine monomers in N,N-dimethylformamide, preparing a nanofiber membrane rich in one monomer by electrospinning, and then in situ growing a fluorinated covalent organic framework on the nanofiber membrane by a Schiff base reaction with tetrafluoroterephthalaldehyde monomer, and drying and hot pressing to obtain a nanofiber membrane based on a fluorinated covalent organic framework; Step 2: preparing a precursor solution consisting of dioxolane, ethylene glycol dimethyl ether, fluorinated ethylene carbonate, and lithium salt; Step 3: Add the precursor solution into the covalent organic framework nanofiber membrane to carry out an in-situ polymerization reaction to obtain the composite quasi-solid electrolyte.
2. The method for preparing a composite quasi-solid electrolyte based on a covalent organic framework nanofiber membrane according to claim 1, characterized in that: In the step 1, the mass fraction of polyacrylonitrile is 10%-15%, and the ratio of polyacrylonitrile to 2,4,6-tris(4-aminophenyl)-1,3,5-triazine monomer is 2:1, 1:1 or 1:
2.
3. The method for preparing a composite quasi-solid electrolyte based on a covalent organic framework nanofiber membrane according to claim 1, characterized in that: The electrospinning rate in step 1 was set to 0.5-2 mL h -1 , the operating voltage is 10-20kV, and the distance between the needle and the collector is 10-20cm.
4. The method for preparing a composite quasi-solid electrolyte based on a covalent organic framework nanofiber membrane according to claim 1, characterized in that: In step 1, the specific step of in-situ growth is to dissolve 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and tetrafluorobenzaldehyde in 8 mL of n-butanol, 8 mL of o-dichlorobenzene and 0.8 mL of acetic acid (12 mol L -1 ) as the reaction liquid, then put the monomer fiber membrane and the reaction liquid into a reactor for reaction at 60-150° C. for 1-7 days, and rinse and soak with tetrahydrofuran, methanol and n-hexane for three times.
5. The method for preparing a composite quasi-solid electrolyte based on a covalent organic framework nanofiber membrane according to claim 1, characterized in that: The molar ratio of the content of 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine in the reaction solution and the monomer fiber membrane is 1:1, and the molar ratio of 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine to tetrafluorobenzaldehyde in the entire reaction system is 1:1.
5.
6. The method for preparing a composite quasi-solid electrolyte based on a covalent organic framework nanofiber membrane according to claim 1, characterized in that: In the step 2, the volume fraction of dioxolane is 50%-80%, the volume fraction of ethylene glycol dimethyl ether is 10%-40%, and the volume fraction of fluorinated ethylene carbonate is 10%.
7. The method for preparing a composite quasi-solid electrolyte based on a covalent organic framework nanofiber membrane according to claim 1, characterized in that: The lithium salt in step 2 is lithium bis(trifluoromethylsulfonyl)imide and lithium hexafluorophosphate, and the concentration of the two is 0.5-1 mol L -1 .
8. The method for preparing a composite quasi-solid electrolyte based on a covalent organic framework nanofiber membrane according to claim 1, characterized in that: The temperature of the in-situ polymerization in step 3 is 30-60° C., and the reaction time is 2-24 hours.
9. A composite quasi-solid electrolyte based on a covalent organic framework nanofiber membrane prepared according to the method of any one of claims 1-8.
10. An application of the composite quasi-solid electrolyte based on covalent organic framework nanofiber membrane according to claim 9 in a solid-state lithium battery, characterized in that: The solid-state lithium battery comprises the composite quasi-solid electrolyte, positive electrode material, and negative electrode material as described in any one of claims 1 to 9, wherein the positive electrode material comprises any one of lithium iron phosphate or nickel-cobalt-manganese ternary material electrodes, and the negative electrode material comprises any one of metallic lithium, graphite, and silicon-carbon negative electrodes.